2012
DOI: 10.3109/0886022x.2012.687346
|View full text |Cite
|
Sign up to set email alerts
|

Hair Dye Related Acute Kidney Injury – A Clinical and Experimental Study

Abstract: We studied paraphenylenediamine (PPD)-related acute kidney injury (AKI) in 81 patients and also in albino rats experimentally. In the patients' group AKI was found in 32.7%. Of them, 81.4% needed dialysis support. The overall mortality was 25.9%. In experimental rats the renal lesions were noted in all and they were glomerular congestion, intertubular (interstitial) hemorrhages, acute tubular necrosis, mesangial proliferation, and intratubular casts. The severity of renal injury appears to be dose dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Animal experiments revealed that approximately one-third of colorants disappeared from the skin within weeks after tattooing [ 32 ]. Furthermore, acute and chronic PPD poisoning in humans has caused renal, hepatic, and cardiac complications [ 15 , 33 ]. Further assessment of the health risk of PPD is imperative due to its widespread application, despite the low risk from the use of commercialized PPD-contained products.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Animal experiments revealed that approximately one-third of colorants disappeared from the skin within weeks after tattooing [ 32 ]. Furthermore, acute and chronic PPD poisoning in humans has caused renal, hepatic, and cardiac complications [ 15 , 33 ]. Further assessment of the health risk of PPD is imperative due to its widespread application, despite the low risk from the use of commercialized PPD-contained products.…”
Section: Discussionmentioning
confidence: 99%
“…The highest PPD-derived radioactivity was present in the muscle, skin, and liver of rodents after exposure, while clearance of PPD-derived radioactivity was primarily through the urine (68-86%) and secondarily through the feces (10-19%) [ 34 ]. Previous studies demonstrated that PPD led to acute renal failure [ 15 ] and impaired urothelial cells through ROS-mediated apoptosis and autophagy formation [ 17 19 ]. Our data suggested that toxic metabolites from PPD might impair renal tubular cells by inhibiting water absorption, resulting in early stage diuresis and late-stage oliguria with damaged urothelial cells leading to frequent urination by undefined mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations